2020
DOI: 10.1002/adhm.202000895
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial Based Strategies for Engineering New Lymphatic Vasculature

Abstract: The lymphatic system is essential for tissue regeneration and repair due to its pivotal role in resolving inflammation, immune cell surveillance, lipid transport, and maintaining tissue homeostasis. Loss of functional lymphatic vasculature is directly implicated in a variety of diseases, including lymphedema, obesity, and the progression of cardiovascular diseases. Strategies that stimulate the formation of new lymphatic vessels (lymphangiogenesis) could provide an appealing new approach to reverse the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 215 publications
(292 reference statements)
0
16
0
Order By: Relevance
“…In contrast, the Ce-MBGNs group led to remarkably enhanced tube formation in comparison to the control and MBGNs group. Moreover, the quantitative analysis of the number of formed tubes (Figure 6b) indicated that Ce-MBGNs could improve lymphatic vascular network formation to a greater extent than VEGF-C (50 ng/mL), which is a well-known growth factor able to stimulate lymphatic vascular network formation [15].…”
Section: Ce-mbgns Improved Lymphatic Vascular Network Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the Ce-MBGNs group led to remarkably enhanced tube formation in comparison to the control and MBGNs group. Moreover, the quantitative analysis of the number of formed tubes (Figure 6b) indicated that Ce-MBGNs could improve lymphatic vascular network formation to a greater extent than VEGF-C (50 ng/mL), which is a well-known growth factor able to stimulate lymphatic vascular network formation [15].…”
Section: Ce-mbgns Improved Lymphatic Vascular Network Formationmentioning
confidence: 99%
“…Expression of VEGFR-3 can be found in all endothelia during development, but later, VEGFR-3 becomes mainly found in lymphatic cells [15]. VEGFR-3 is thought to play a significant role in the proliferation and migration of LECs [39].…”
Section: Ce-mbgns Regulated Lymphangiogenesis Through the Hif-1α/vegfr-3 Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…11 Tissue engineering has witnessed remarkable advancement in various fields of medicine and has the potential of revolutionizing the management of lymphedema. [12][13][14][15][16] Combining approaches of biotechnology with the evolving understanding of lymphangiogenesis may offer promising treatment modalities for patients suffering from lymphedema. 17 This review will summarize the current approach to cancer-related lymphedema and advances in lymphatic tissue engineering strategies (Fig.…”
Section: Introductionmentioning
confidence: 99%